«Se tu leggi sempre così». Gli esordi di Gadda come critico letterario - Roberta Colbertaldo (Annali Online dell'Università di Ferrara. Sezione Lettere)
The correspondences of Carlo Emilio Gadda with his first Florentine publishers ‒ which have been edited and commented in my PhD thesis ‒ reveal some important contextual and topical elements for the understanding of his early production. In particular, his activity as a literary critic in the years between the two world wars gains a new significance and a new place through these correspondences.